X-box binding protein 1: A new metabolic mediator and drug target of metformin? - Lou, Kai; Sun, Pei; Zhang, Chunxue; Jiang, Qiang; Pang, Shuguang (Frontiers in Pharmacology, 2022)
Accumulating evidence has demonstrated that metformin improved hypertriglyceridemia. The present study aim to investigate the molecular mechanism by which metformin improves hypertriglyceridemia via regulation of diacylglycerol O-acyltransferase 2 (DGAT2) and X-box binding protein 1 (XBP1) in the liver and whether AMP-activated protein kinase (AMPK) is involved. Mice were fed a high-fat diet (HFD) or high-fat diet with metformin for 5 weeks to evaluate the effect of metformin on triglyceride (TG) levels and expression of DGAT2 and XBP1 in the liver. In vitro HepG2 cells or XBP1 knockout AML12 hepatocytes were stimulated with metformin, palmitic acid or small interfering RNA inducing XBP1 knockdown, or dominant-negative mutant AMPK plasmid. Metformin treatment reduced hepatic TG levels in the liver of HFD-fed mice. Expression of nuclear and cytoplasmic XBP1 protein and its downstream target gene DGAT2 decreased in the liver of HFD-fed mice and HepG2 cells after metformin treatment. AMPK inactivation or overexpression of XBP1 attenuates this effect. Our preliminary results demonstrate that metformin activates AMPK to reduce TG synthesis by inhibiting the XBP1-mediated DGAT2 pathway, at least in part, suggesting that XBP1 is a new metabolic mediator for metformin treatment of hypertriglyceridemia and associated metabolic disease.